Still Matters! Kurdish EFL Learners' Perceptions towards Non-Native English Teachers’ Pronunciation Skills - Mahmood, Rizgar Qasim (Círculo de Lingüística Aplicada a la Comunicación, 2024)
Pronunciation is the fundamental aspect of a spoken message (Pennington & Rogerson-Revell, 2018). Although there are at least four non-native speakers of English for every native speaker (Braine, 2010), and this rate is still increasing, the issue of non-native speakers (NNS) English teachers has not been resolved. This paper reports on a study carried out in Iraqi Kurdistan which explored the perceptions of undergraduate university students towards their non-native English teachers. The students were asked to complete an online questionnaire. After the data analysis process, although the results show that the students have shown positive perceptions towards their NNS English teachers; third-year students had less favorable perceptions than second-year students. The reasons for the students’ different perceptions are discussed. On the whole, most of the participants believed that NNESTs, including Kurdish EFL teachers, can teach pronunciation courses, but they need to be trained before teaching this skill. The findings suggest pedagogical implications for ESL/EFL teachers and learners during teaching and learning pronunciation skills.
Keywords: Kurdish EFL learners; NNSTs; pronunciation; speaking skills; teaching L2